Circuit Training is More Effect than Interval Training on Increasing VO2 Max in Football Players: Latihan Sirkuit lebih Efektif daripada Latihan Interval dalam Meningkatkan VO2 Max pada Pemain Sepakbola - Nurhayati, Ummy Aisyah; Hasnawati, Baiq Nurul (Ikatan Fisioterapi Indonesia, 2023)
Introduction: Football players should be in good physical condition to support their performance on the field. This includes cardiorespiratory fitness (VO2 max), which needs to be maintained to be able to perform while playing. An increase in VO2 max is an indication of the ability of the heart and lungs to function optimally during exercise. Low endurance can cause football players to tire easily. Exercises that can be done to increase VO2 max are circuit training and interval training. Circuit training has a physiological effect on the muscles. They adapt and are automatically able to increase the maximum oxygen volume. Whereas interval training has an effect on metabolic waste from muscles at rest, resulting in increased oxygen consumption during exercise and an increase in VO2 max. Research objective: To know the difference in the effect of circuit training and interval training on the increase of the VO2 max in football players. Methods: Experimental with a quasi-experimental approach to pre- and post-test two grub design treatment, sampling technique using total sampling, a sample of 44 people with a training program 3x a week for 6 weeks. The research instrument used was a multi-stage fitness test. Data analysis used was descriptive statistical test, normality test, homogeneity test and hypothesis testing. Results: Hypothesis tests I and II using paired sample t-test showed that there was an effect of circuit training and interval training on the increase of VO2 max in football players (P=0.00 P<0.05). Hypothesis test III using independent samples t-test shows that circuit training has a greater effect than interval training on increasing VO2 max in footballers (P=0.00 P<0.05). Conclusion: Circuit training is more effective than interval training in increasing VO2max. Suggestion: Further analysis of other more varied exercises to increase VO2 max is expected in future research.